Lung volumes and maximal respiratory pressures in collegiate swimmers and runners - Cordain, L.; Tucker, A.; Moon, D.; Stager, J. M. (Research Quarterly for Exercise and Sport, 1990)
This study attempted to determine if respiratory muscle strength was related to pulmonary volume differences in athletes and non-athletes. Subjects were 11 female swimmers, 11 female cross-country runners, and two non-athletic control groups. Variables measured were maximal inspiratory pressure and maximal expiratory pressure as well as vital capacity, residual lung volume, inspiratory capacity, and functional residual capacity. Swimmers were larger than the other three groups in: 1) vital capacity, 2) residual lung volume, 3) inspiratory capacity, and 4) functional residual capacity. There was no difference in either maximal inspiratory pressure or inspiratory flow. Timed expiratory volumes were significantly lower for swimmers than the other groups. These data suggest that adaptive growth may be responsible, in part, for the augmented static lung volumes demonstrated in swimmers. Implication: This study yields possible support for the belief that breathing capacities develop in athletes who partake of swimming. It may support the advocacy of medical benefits to be derived from the sport for respiratory problem persons (e.g., asthmatics). Much more work needs to be conducted before this assertion can be confirmed or denied.